Factors Related to Significant Improvement of Estimated Glomerular Filtration Rates in Chronic Hepatitis B Patients Receiving Telbivudine Therapy - Te-Fu Lin; Ping-I Hsu; Kung-Hung Lin; Feng-Woei Tsay; Tzung-Jiun Tsai; Yan-Hua Chen; Hsien-Chung Yu (Gastroenterology Research and Practice)
Background and Aim. The improvement of estimated glomerular filtration rates (eGFRs) in chronic hepatitis B (CHB) patients receiving telbivudine therapy is well known. The aim of this study was to clarify the kinetics of eGFRs and to identify the significant factors related to the improvement of eGFRs in telbivudine-treated CHB patients in a real-world setting. Methods. Serial eGFRs were calculated every 3 months using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. The patients were classified as CKD-1, -2, or -3 according to a baseline eGFR of ≥90, 60–89, or <60 mL/min/1.73 m2, respectively. A significant improvement of eGFR was defined as a more than 10% increase from the baseline. Results. A total of 129 patients were enrolled, of whom 36% had significantly improved eGFRs. According to a multivariate analysis, diabetes mellitus (DM) (p=0.028) and CKD-3 (p=0.043) were both significantly related to such improvement. The rates of significant improvement of eGFR were about 73% and 77% in patients with DM and CKD-3, respectively. Conclusions. Telbivudine is an alternative drug of choice for the treatment of hepatitis B patients for whom renal safety is a concern, especially patients with DM and CKD-3.